Validation of test performance characteristics and minimal clinically important difference of the 6-minute walk test in patients with idiopathic pulmonary fibrosis. Issue 7 (July 2015) - Nathan, Steven D.; du Bois, Roland M.; Albera, Carlo; Bradford, Williamson Z.; Costabel, Ulrich; Kartashov, Alex; Noble, Paul W.; Sahn, Steven A.; Valeyre, Dominique; Weycker, Derek; King, Talmadge E.
Summary: Background: The 6-minute walk test distance (6MWD) has been shown to be a valid and responsive outcome measure in patients with idiopathic pulmonary fibrosis (IPF). The analyses were based, however, on a single phase 3 trial and require validation in an independent cohort. Objective: To confirm the performance characteristics and estimates of minimal clinically important difference (MCID) of 6MWD in an independent cohort of patients with IPF. Methods: Patients randomized to placebo in the phase 3 CAPACITY trials who had a baseline 6MWD measurement were included in these analyses. The 6MWD and other functional parameters (lung function, dyspnea, and health-related quality of life) were measured at baseline and 24-week intervals. Validity and responsiveness were examined using Spearman correlation coefficients. The MCID was estimated using distribution- and anchor-based methods. Results: The analysis comprised 338 patients. Baseline 6MWD was significantly correlated with lung function measures, patient-reported outcomes, and quality-of-life measures (validity). Compared with baseline 6MWD, change in 6MWD (responsiveness) showed stronger correlations with change in lung function parameters and quality-of-life measures. Dyspnea measured by the University of California San Diego Shortness of Breath Questionnaire showed the strongest correlations with 6MWD (baseline: coefficient −0.35; 48-week change: coefficient −0.37; both p < 0.001). The distribution-based analyses of MCID using standard error of measurement yielded an MCID of 37 m, and distribution-based analyses by effect size resulted in 29.2 m. The MCID by anchor-based analysis using criterion referencing (health events of hospitalization or death) was 21.7 m. Conclusions: The 6MWD is a valid and responsive clinical endpoint, which provides objective and clinically meaningful information regarding functional status and near-term prognosis. These results confirm previous findings in an independent cohort of patients with IPF.